التأثيرات الخارجية على معتقدات أهل کوش - د. صديق مهدي عبد الرحمن; د. عبد الله الزبير يوسف (White Nile Journal for Studies and Research, 2017)
This study aims at knowing the effects of external beliefs on Kosh and their influence in the religious rituals, likewise the rites in the religious architecture as in the temples burying the dead ....etc .The significance of this study lies in highlighting the pillars effects of external beliefs particularly the Egyptians. The researcher followed the historical research method; with all its analysis, comparison, criticism, and procedures like description results according to the study. The researcher has come out with the following results 1-Transition of worship, for the Gods Osiris and Isis from Egypt to Sudan for mutual cultures. 2-The Nobatians has chosen the God Amon of all the Gods to worship. 3-Temples exemplified the main place from which the religious authority rules, commands were carried out by the priests and bishops, who were supposed to have religious knowledge and the truth.